Subcontractors in Public Procurement: An Analysis of Potential Risks and Fraud Factors in Procurement Practices in Indonesia - Shakira, Talitha Atha; Marsal, Irsyaf (International Journal of Social Service and Research, 2026)
Government procurement of goods and services (pengadaan barang dan jasa or PBJ) constitutes a strategic sector while simultaneously being one of the most vulnerable to corruption. Monitoring data from ICW in 2023 recorded 791 corruption cases, causing state losses amounting to IDR 28.4 trillion, with the most dominant modus operandi being fictitious projects and falsified accountability reports. One critical loophole lies in the subcontracting mechanism, which is frequently misused through the inclusion of fictitious subcontractors. This research employs a normative juridical method using a statutory approach and case study analysis. The analysis focuses on the Decision of the High Court of Bandung No. 5/Pid.Sus-TPK/2024/PT BDG (Amarta Karya case) and the Decision of the Central Jakarta District Court No. 59/Pid.Sus-TPK/2020/PN.Jkt.Pst in conjunction with the Supreme Court Decision No. 944 K/Pid.Sus/2022 (Waskita Karya case), in connection with LKPP Regulation No. 12 of 2021, the theory of cashflow fraud in contractual chains, and the “don’t care” theory in contractual relations. The findings demonstrate that subcontract fraud arises due to weak factual verification, lengthy contractual chains that enable fictitious invoices, and the limited authority of the Budget User (PA) in supervising subcontractors. Subcontract fraud is not only categorized as a criminal act of corruption but may also be qualified as a breach of contract (wanprestasi) under civil law.